Effect of Emulsification Process on Multiple Lipid Particles Encapsulating Both Coenzyme Q10 and Tea Polyphenols. Issue 2 (15th October 2014) - Zhao, Guodong; Hu, Caibiao; Sun, Rui; Ni, Shilei; Xia, Qiang
Abstract: A novel drug delivery system called multiple lipid particles containing both coenzyme Q10 and tea polyphenols were proposed for the stabilization of water‐in‐oil‐in‐water emulsions. The effects of the type and concentration of lipophilic and hydrophilic emulsifier, and drug concentration on multiple lipid particles were investigated. The experimental results revealed that it is possible to stabilize the primary emulsions of multiple lipid particles with mixtures of lecithin, polyglycerol polyricinoleate and PEG 30 dipolyhydroxystearate. Polyglyceryl‐10 laurate as proper hydrophilic emulsifier exhibited terrific compatibility with polyglycerol polyricinoleate. In vitro release study displayed a sustained drug release and the obtained outcomes also suggested that multiple lipid particles could enhance loading capacity of both lipophilic and hydrophilic drugs with high level of encapsulation efficiency and long‐term stability. Practical Applications: Multiple emulsions are a complex system that could incorporate both lipophilic and hydrophilic drugs. However, the destabilization of multiple emulsions with time limits their application. To obtain a stable formulation for encapsulation of both lipophilic and hydrophilic drugs, a novel drug delivery system, called multiple lipid particles, was proposed, which combines the advantages of multiple emulsions and solid lipid nanoparticles. This study investigated the emulsification process of multiple lipid particles to obtain stable formulation. The results revealed that multiple lipid particles could encapsulate both lipophilic and hydrophilic drugs with high loading capacity and encapsulation efficiency. The solid state of multiple lipid particles is more stable than that of multiple emulsions. Thus, multiple lipid particles have potential application in food, cosmetics and pharmaceutical industries.